533The psychosocial profiles of children aged 11-12 years who have self-harmed: A prospective cohort study. (2nd September 2021) - Borschmann, Rohan; Mundy, Lisa; Canterford, Louise; Moreno-Betancur, Margarita; Moran, Paul; Allen, Nicholas; Viner, Russell; Degenhardt, Louisa; Kosola, Silja; Fedyszyn, Izabela; Patton, George
Abstract: Background: Self-harm in very young people can be a clinically ominous event. While most studies to date have focused on self-harm during the teenage years, fewer studies have examined children aged 12 years or under. We aimed to estimate the incidence and correlates of recent self-harm in a population-based, non-treatment-seeking sample of primary school-aged children. Methods: 1059 children from 43 primary schools in Melbourne, Australia were interviewed at the age of 8 years (Wave 1), and followed up annually until the age of 11 years (Waves 2-4). Interviews covered a range of physical and mental health, social, educational and family domains, including (at Wave 4) self-harm during the previous 12 months. Results: At Wave 4 (mean age: 11.9 years), a total of 28 children (3%; 18 girls [3%], 10 boys [2%]) reported self-harming during the previous 12 months. When compared with children who reported no self-harm, they were more likely to report depression, anxiety, poor emotional control, frequent bullying victimisation (including online bullying), truancy, recent alcohol consumption, and antisocial behaviour during Waves 1-3. They were also more likely to report having few friends. Conclusions: Self-harm was reported by a proportion of community-dwelling children aged 11-12 years. As these children were more likely to report a range of other adverse behaviours, experiences and health conditions, clinicians should consider the possibility of prior self-harm when assessing children presenting with such behaviours and issues. Key messages: The focus of intervention efforts aimed at preventing and reducing adolescent self-harm should extend to primary school-aged children, with a focus on mental health and peer relationships during the pubertal transition.